Interferon‐gamma release assays can effectively screen migrants for the tuberculosis infection, but urgent, active cases need clinical recognition. (8th April 2016) - Nejat, Sahar; Bennet, Rutger
Abstract: Aim: Increasing numbers of migrants to Sweden are screened for tuberculosis (TB), and a rational approach to screening is required. We evaluated positive tuberculin skin tests (TSTs) and interferon‐gamma release assays (IGRAs) on paediatric migrants in relation to the TB incidence in the corresponding foreign‐born populations in Stockholm. Methods: This study examined the characteristics of migrants under the age of 18 who were referred to a paediatric TB clinic at Karolinska University Hospital from 2008 to 2014 by primary care centres in Stockholm County. Results: We saw 943 TST‐positive children with a median age of 14 years at the TB clinic and performed IGRAs on 557. IGRA positivity ranged from 64% in migrants from Somalia to 20% in those from the former Soviet Union and eastern Europe, with an estimated population level prevalence of 18.8% and 4.2%, respectively. These were significantly correlated to TB incidence in foreign‐born Stockholm children. We diagnosed active TB in 20 screened migrants, and advanced, symptomatic TB was diagnosed in 10 recently arrived migrants without screening. Conclusion: IGRAs showed higher specificity than TST in identifying tuberculosis. TB screening should focus on migrants from high‐incidence countries, but this may be inadequate to detect advanced TB cases. Abstract :